2017
DOI: 10.1007/s12602-017-9308-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milk Fermented with Lactic Acid Bacteria on Diarrheal Incidence, Growth Performance and Microbiological and Blood Profiles of Newborn Dairy Calves

Abstract: The effect of the administration of milk fermented with lactic acid bacteria to calves was evaluated. The strains included were: Lactobacillus murinus CRL1695, Lact. mucosae CRL1696, Lact. johnsonii CRL1693, and Lact. salivarius CRL1702, which were selected for their beneficial and functional properties and isolated from healthy calves in the northwestern region of Argentina. The trial was conducted on a dairy farm located in Tucumán (Holando-Argentino calves). A randomized controlled trial was performed in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 48 publications
3
19
1
Order By: Relevance
“…Similarly, improved hemoglobin (110.0 vs. 98.0 g/L) was observed at the end of the experiment on 20 ml direct oral fed microbes (Propionibacterium jensenii) in Holstein bull-calves (Adams et al, 2008). Contrary to the present study, Maldonado et al (2018) reported non-significantly lower hemoglobin (144 ± 13 vs. 147 ± 42 g/L) in calves fed milk fermented with lactic acid bacteria at 1 × 10 9 CFU/calf. Like present finding on enzyme feeding in calves, the feeding of Jersey x Kankrej lactating cows with live yeast and cocktail of enzymes (xylanase, phytase, cellulase, p-glucanase, pectinase, amylase, protease, a-galactosidase, P-galactosidase and lipase) and only cocktail of enzymes for the period of 24 weeks did not alter the haemoglobin level (Vahora, 2004), while Ghazanfar et al (2015) showed improved (p < 0.05) hemoglobin (13.26 ± 1.20 vs. 9.76 ± 0.55 g/dL) in dairy heifers fed dietary supplementation of yeast (Saccharomyces cerevisiae Yea-Sac 1026 ) at 5 g/day.…”
Section: Results a N D Discussioncontrasting
confidence: 67%
“…Similarly, improved hemoglobin (110.0 vs. 98.0 g/L) was observed at the end of the experiment on 20 ml direct oral fed microbes (Propionibacterium jensenii) in Holstein bull-calves (Adams et al, 2008). Contrary to the present study, Maldonado et al (2018) reported non-significantly lower hemoglobin (144 ± 13 vs. 147 ± 42 g/L) in calves fed milk fermented with lactic acid bacteria at 1 × 10 9 CFU/calf. Like present finding on enzyme feeding in calves, the feeding of Jersey x Kankrej lactating cows with live yeast and cocktail of enzymes (xylanase, phytase, cellulase, p-glucanase, pectinase, amylase, protease, a-galactosidase, P-galactosidase and lipase) and only cocktail of enzymes for the period of 24 weeks did not alter the haemoglobin level (Vahora, 2004), while Ghazanfar et al (2015) showed improved (p < 0.05) hemoglobin (13.26 ± 1.20 vs. 9.76 ± 0.55 g/dL) in dairy heifers fed dietary supplementation of yeast (Saccharomyces cerevisiae Yea-Sac 1026 ) at 5 g/day.…”
Section: Results a N D Discussioncontrasting
confidence: 67%
“…In dairy industry, calf diarrhea has been causing considerable economic losses because of calf mortality, weight loss in surviving calves all over the world, including Hokkaido. Several probiotics have been used as preventive or supportive therapy for dairy cattle and neonatal calf for a long time, and previous reports indicated the bene t calf performance and health [14][15][16][17][18][19][20][21][22][23][24][25]. Fermented milk, an old probiotics for dairy cattle, provides several clinical bene ts for calf breeding, and has been widely used as economical and safe probiotics [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Fermented milk includes the rich amino acids required for calf growth, and has been used for many years in the dairy industry [26][27][28]. A recent report indicates that the fermented milk enhanced nutritional parameters such as height, weight, and body performance [24]. In addition, the feeding of fermented milk reduced in diarrhea mobility and mortality [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no study has evaluated the effects of dietary supplementation of live yeast on mastitis and milk microorganism based on the high-throughput sequencing, a new method that provide a more complete relative qualification of micro community composition. Lactic acid bacteria (LAB) is also shown as potential probiotics for therapeutic use against endometrial inflammation and mastitis and prevention for diarrhea in calf, which is capable for the ability to strengthen systemic immune function (Genis et al 2017;Bouchard et al 2015;Maldonado et al 2017). Intramammary LAB incubation increased the amounts of IgG isotypes in blood and milk, as well as lymphocyte proliferation and negative the major bovine mastitis pathogens on dry-off cows, which suggests restored balance in microbiota of the mammary gland and improved systemic immune function (Pellegrino et al 2017).…”
Section: Introductionmentioning
confidence: 99%